Processamento e avaliação físico-química de madeira sintética de blendas extrudadas com politereftalato de etileno (PET) e lignina kraft - Luiz, Franciele Natividade (2016)
Polyethylene terephthalate (PET) is a thermoplastic polyester widely used in a variety of industrial processes, especially beverages, which, when improperly disposed of, becomes an environmental liability, leading to environmental pollution, loss of local biodiversity and even Proliferation of disease vectors. In the search for options to minimize environmental impacts from the disposal of polymeric materials, the production of polymer blends is an alternative, which can still add value to other industrial byproducts, such as lignin. Lignin is one of the predominant biopolymers in plants, such as cellulose and hemicellulose, has high availability, and can be obtained through waste from the paper and cellulose industry. In order to add value to these residues, in this study, crystal virgin PET containers, obtained from preforms, crushed and sanitized, and kraft lignin (LK) obtained by purification of black liquor, Paper and pulp for the formation of blends. The blends were extruded at contents of 1, 2, 5 and 10% LK/PET (m/m). Subsequently, the thermal characteristics were investigated by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) and chemical and morphological characteristics with X-ray diffraction (XRD), infrared spectroscopy (FTIR) and electron microscopy of Scanning (SEM). Under the conditions of this study, PET/LK systems lower than 10% showed better mechanical stability, less alteration of the crystalline profile, interaction and miscibility in the blends. Since the use of the residual mass of paper industries (kraft lignin) becomes a promising alternative in the production of substitutes for wood, due to the relative ease and the low cost of obtaining, as well as the amount of raw material available, both of LK and of PET discarded, resulting in the valorization of these two residues.